Exploring Design-Based Research: Enhancing Methodologies for Educational Innovation - Awang Najib, Awang Mohamad; Zaimuariffudin Shukri, Nordin; Mohd Hafizan, Hashim (College of Education Fayetteville State University, 2025)
Design-based research (DBR) has proven to be a robust methodology for transforming educational practice through a systematic cycle of analysis, design, development, and real-world implementation. Its distinctive strength lies in fostering close collaboration between researchers and educators within authentic learning contexts, producing design principles and theories that are deeply responsive to local needs. This paper presents a critical and comprehensive examination of the three core phases of the McKenney and Reeves (2012) generic DBR model, illustrating how it integrates rigorous inquiry with practical problem-solving. It also introduces Sandoval's (2014) concept of conjecture mapping as a strategic tool for aligning theoretical assumptions with design decisions, thereby strengthening the explanatory power of DBR studies. The discussion is grounded in three diverse applications of DBR in educational technology, including blended learning in higher education, computational thinking in elementary science, and digital escape rooms in medical education, showcasing how iterative, context-sensitive design can generate both practical innovations and theoretical insights.